Contribution of the alternative model for DSM-5 personality disorders to relationship satisfaction - Savard, Claudia; Deschênes, Mélissa; Gagné-Pomerleau, Élodie; Payant, Maude; Mayrand, Kristel; Nolin, Marie-Chloé; Marcoux, Louis-Alexandre; Gamache, Dominick (Frontiers in Psychiatry, 2024)
Introduction Personality is a central factor associated with relationship discord, conflicts, and separation, as well as with dyadic adjustment and relationship stability. The Alternative Model for Personality Disorders (AMPD) of the DSM-5 offers a hybrid model for understanding personality based on personality dysfunction (Criterion A) and pathological domains and facets (Criterion B). So far, few studies have integrated this model into the understanding of relationship quality. Therefore, the aim of this study was to examine the contribution of Criterion B to relationship satisfaction in individuals involved in an intimate relationship. We also explored the joint contribution of Criteria A and B, as well as their interaction effects, to relationship satisfaction. Methods Participants were drawn from two clinical samples: patients with personality disorders (PD; N = 101) and clients consulting in private practice clinics (PPC; N = 350). They completed self-report questionnaires assessing relationship satisfaction and AMPD Criteria A (only for PPC sample) and B. Results Hierarchical regressions showed that, for the PD sample, the Detachment and Negative Affectivity domains, especially the pathological facets of Intimacy Avoidance and Separation Insecurity, explained 22.5% of relationship satisfaction’s variance. For PPC clients, Detachment, Negative Affectivity, and Antagonism domains, and especially the pathological facets of Intimacy Avoidance, Anxiousness, and Grandiosity, contribute significantly to relationship satisfaction, explaining 14.8% of its variance. Criterion A elements did not evince incremental value to the regression models in the PPC sample, and no Criteria A and B interaction effects were found. Clinical implications as well as limitations of the study are discussed.